DISPUTE RESOLUTION OF DESTROYED MORTGAGE GUARANTEE (Case Study of Petobo Village, South Palu District, Palu City) - Maisa Maisa; Haerani Husaniy (Omnibus Law Journal, 2021)
This study aims to determine the legal status of the destroyed mortgage object and to determine the dispute over the destroyed mortgage object. The research method used in this paper is the empirical normative method and qualitative data analysis. The results of this study are when a liquefaction disaster causes the object of the mortgage to be destroyed, the debtor's responsibility ends when the object of the mortgage is destroyed as regulated in Law Number 5 of 1960 article 27 b, the Mortgage Law, the abolition of property rights if the land is destroyed. and Creditors in handling or providing solutions to disputes over the destruction of the object of mortgage guarantee, namely the granting of relaxation or delay by the State Savings Bank. Suggestion, It is better for the government as soon as possible to make a policy for the sake of legal stability again in order to create legal certainty related to the dispute. And the creditor should make a rule which relates to the settlement of disputes over collateral objects that were destroyed due to liquefaction after the previous relaxation policy so that in the future this can be a guide or reference by the parties concerned easily without any hesitation with the existence of legal certainty.